2007
DOI: 10.1073/pnas.0610158104
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic speciation in a model invertebrate chordate

Abstract: We applied independent species concepts to clarify the phylogeographic structure of the ascidian Ciona intestinalis, a powerful model system in chordate biology and for comparative genomic studies. Intensive research with this marine invertebrate is based on the assumption that natural populations globally belong to a single species. Therefore, understanding the true taxonomic classification may have implications for experimental design and data management. Phylogenies inferred from mitochondrial and nuclear D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
218
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(227 citation statements)
references
References 54 publications
7
218
0
Order By: Relevance
“…The genetic divergences recorded between these lineages (10.8-16.5% COI divergence), corresponding to about 4.3-11.0 Myr of divergent evolutionary history (1.5-2.5% per Myr [42]), are significant. These levels far exceed COI divergences reported between cryptic species of other colonial tunicates, like Pseudodistoma crucigaster (2.12% [43]), Clavelina lepadiformis (5% [44]) or Pycnoclavella communis (8.55% [45]), and are comparable with those identified between widely recognized cryptic species of the solitary tunicate Ciona intestinalis (11.1-18.4% [10,46,47]). Furthermore, the complete lack of contemporary gene flow between clades, even in locations where their distribution intersects (figure 4), suggests that reproductive isolation is probably complete.…”
Section: Discussionmentioning
confidence: 64%
“…The genetic divergences recorded between these lineages (10.8-16.5% COI divergence), corresponding to about 4.3-11.0 Myr of divergent evolutionary history (1.5-2.5% per Myr [42]), are significant. These levels far exceed COI divergences reported between cryptic species of other colonial tunicates, like Pseudodistoma crucigaster (2.12% [43]), Clavelina lepadiformis (5% [44]) or Pycnoclavella communis (8.55% [45]), and are comparable with those identified between widely recognized cryptic species of the solitary tunicate Ciona intestinalis (11.1-18.4% [10,46,47]). Furthermore, the complete lack of contemporary gene flow between clades, even in locations where their distribution intersects (figure 4), suggests that reproductive isolation is probably complete.…”
Section: Discussionmentioning
confidence: 64%
“…For instance, Ciona intestinalis (Linnaeus, 1767) is a model organism in evolutionary developmental biology and was among the first animals to have its genome fully sequenced (Dehal et al 2002). However, this taxon was recently revealed as a complex of four cryptic species (Suzuki et al 2005;Caputi et al 2007;Nydam & Harrison 2007;Zhan et al 2010), including two widespread species that diverged ca. 3-4 Ma ago (Roux et al 2013) and are not yet formally named.…”
mentioning
confidence: 99%
“…Notably, genetic surveys have made clear that cryptic speciation is very common in invasive ascidians (e.g., Caputi et al 2007;Pérez-Portela et al 2009Zhan et al 2010;Bock et al 2012). Interestingly, in at least three of these cryptic species complexes, namely C. intestinalis (Zhan et al 2010), B. schlosseri , and Diplosoma listerianum (Pérez-Portela et al 2013), one or a limited number of sister taxa have been inferred as being invasive, while the rest appear to be highly geographically restricted.…”
Section: Interspecific Genetic Diversitymentioning
confidence: 99%
“…Many studies clearly demonstrated that invasive ascidians decreased species richness and changed biodiversity of invaded habitats (see review by Aldred and Clare 2014). Once non-indigenous ascidians become established in new Lambert (1998), Carver et al (2003), Blum et al (2007), Caputi et al (2007), Lambert (2007), Harrison (2007, 2010), Zhan et al (2010) (2008) and Dupont et al (2010) environments, they may overgrow and out-compete native species and finally become dominant members of communities Bullard et al 2007a;Aldred and Clare 2014). In some cases, population explosions of invasive ascidians reduce the abundance of other benthic species, resulting in transformation of community structure (Castilla et al 2004;Rius et al 2009).…”
Section: Negative Impactsmentioning
confidence: 99%